В решении.
Объяснение:
Найдите значение выражений:
1) (3-x)²-x(x-21) = при x= -2,84
= 9 - 6х + х² - х² +21х =
= 9 + 15х =
=9 + 15 * (-2,84) =
=9 - 42,6 = -33,6.
2) d⁷×(d³)⁻¹ = при d= -2
= d⁷ * 1/d³ =
= d⁷/d³ = d⁷⁻³ = d⁴ = (-2)⁴ = 16.
3) a + (2y-a²)/a = при a= -10 и y=19
общий знаменатель а:
= (а*а + 2у - а²)/а =
= (а² + 2у - а²)/а =
=2у/а = 2*19/(-10) = 38/(-10) = -3,8.
x + y = a > x^2 + 2xy + y^2 = a^2 > x^2 + y^2 = a^2 - 2xy
xy = a^2 - 7a + 14 > 2xy = 2a^2 - 14a + 28
=>
x^2 + y^2 = a^2 - (2a^2 - 14a + 28)
x^2 + y^2 = - (a^2 - 14a + 28)
x^2 + y^2 = - (a^2 - 2*7a + 7^2 - 21)
x^2 + y^2 = - (a - 7)^2 + 21 = 21 - (a - 7)^2
(a - 7)^2 ---> 0 > a = 7